Penentuan Aktivitas Spesifik Radionuklida Alam Pada Udara Dan Laju Dosis Efektif Radiasi Gamma Di Kawasan BPTU-HPT Padang Mengatas Sumatera Barat - Novita, Rahmi; Milvita, Dian; Suhariyono, Gatot; Kusdiana, Kusdiana; Hidayat, Maulidia (Jurnal Fisika Unand, 2025)
The measurement of the radionuclides activity in an area contributes to monitor the environment, radiation safety and the public health. The specific activity of natural radionuclides in the air and the effective dose rate of gamma radiation in the air have been determined at the Center of Superior Livestock Breeding and Forage Animal Feed (BPTU-HPT) in Padang Mengatas, West Sumatra. The samples of the radionuclides were acquired by using the High-Volume Air Sampler (HVAS) at 6 different locations for 60 minutes, then they were prepared for 30 days and subsequently counted by utilizing a pre-calibrated gamma spectrometer for 17 hours. Furthermore, the measurement of the gamma radiation dose rate was carried out at all defined locations using a survey meter.  The results show that the specific activity values ​​of natural radionuclides differ each location point. The specific activity values ​​of Th-232 and U-238 were not detected at all sampling locations. Furthermore, the specific activity values of Ra-226 at location points 4 and 5, and Th-228 at location point 5 are above the threshold set by PERKA BAPETEN. No. 16 of 2013, namely 0.05 Bq/m3 and 0.003 Bq/m3. The effective dose rates of gamma radiation obtained at all sampling locations were below the threshold set by PERKA BAPETEN No. 16 of 2013, which is 1 mSv/year